Cell stiffness predicts cancer cell sensitivity to ultrasound as a selective superficial cancer therapy - Eden Bergman; Riki Goldbart; Tamar Traitel; Eliz Amar‐Lewis; Jonathan Zorea; Ksenia Yegodayev; Irit Alon; Sanela Rankovic; Yuval Krieger; Itay Rousso; Moshe Elkabets; Joseph Kost (Wiley, 2021)
Abstract We hypothesize that the biomechanical properties of cells can predict their viability, with Young's modulus representing the former and cell sensitivity to ultrasound representing the latter. Using atomic force microscopy, we show that the Young's modulus stiffness measure is significantly lower for superficial cancer cells (squamous cell carcinomas and melanoma) compared with noncancerous keratinocyte cells. In vitro findings reveal a significant difference between cancerous and noncancerous cell viability at the four ultrasound energy levels evaluated, with different cell lines exhibiting different sensitivities to the same ultrasound intensity. Young's modulus correlates with cell viability (R2 = 0.93), indicating that this single biomechanical property can predict cell sensitivity to ultrasound treatment. In mice, repeated ultrasound treatment inhibits tumor growth without damaging healthy skin tissue. Histopathological tumor analysis indicates ultrasound‐induced focal necrosis at the treatment site. Our findings provide a strong rationale for developing ultrasound as a noninvasive selective treatment for superficial cancers.